Combating Radicalism Through Digital Literacy: Building Resilience At Al-Riyadh Cipanas - Mustikasari, Wiwik; Priyanto; M. Afifuddin (Cita konsultindo, 2026)
Abstract In the era of asymmetric warfare, radicalization no longer develops through face-to-face interaction, but rather through digital propaganda that targets Generation Z by utilizing social media. Islamic boarding schools (pesantren), as traditional Islamic educational institutions, face a fundamental challenge: how to maintain a bastion of moderation when threats come from the digital space, which is difficult to control. This study aimed to analyze how Al Riyadh Cipanas Islamic Boarding School built student resilience through digital literacy as a counter-radicalization strategy. The study used a qualitative approach with an instrumental case study design, involving boarding school caregivers, teachers, and students. Data were collected through in-depth interviews and field observations. Thematic analysis identified three main dimensions: the integration of digital literacy based on Wasatiyah (Islamic moderation) values; the role of teachers as digital gatekeepers and mentors who built trust and guided students through dialogue; and halaqah (discussion circles) as a space for deconstructing digital narratives and developing critical thinking. These three dimensions formed a layered defense and prepared students as agents of digital moderation.